Understanding Consumer Intention To Use Indonesian Electronic Stamp Duty Through Technology Acceptence Model (TAM): Study On PT Peruri Digital Security’s Consumer (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
With the invention of electronic stamps as an extension of adhesive stamps, PT Kertas Padalarang, a subsidiary of Perum Peruri (the company appointed to produce adhesive stamps), has identified a change in consumer behavior where consumers are starting to switch to electronic stamps. This research aims to determine the intention to use electronic stamps using the Technology Acceptance Model (TAM) among the consumers of PT Peruri Digital Security. Using simple random sampling and Slovin techniques, the primary data was collected through online questionnaires from 398 respondents who use electronic stamps. The research method uses a quantitative approach, and the data was analyzed using Partial Least Squares (PLS) with SmartPLS 3 software. The research results show that intention to use electronic stamps is positively and significantly influenced by perceived ease of use, perceived usefulness, and perceived trust. Furthermore, perceived trust can positively and significantly mediate perceived ease of use and perceived usefulness on intention to use.
Keywords: Indonesian Electronic Duty Stamp Paper, Technology Acceptance Model, Marketing Management, Consumer Behavior